Estimates for the volume of the zeros of a holomorphic function depending on a complex parameter. (November 2021) - Kytmanov, A. M.; Sadullaev, A.
Abstract: Given a holomorphic function, , , an estimate for the volume of the zero set is presented which holds uniformly in . Such estimates are quite useful in investigations of oscillatory integrals of the form as . Here is a so-called amplitude function and is a phase function. Bibliography: 9 titles.